PERSEPSI GURU TERHADAP APLIKASI EDMODO SEBAGAI ALAT BANTU KEGIATAN BELAJAR DI SEKOLAH DASAR - Novita Wisudawati; Eko Kuntarto; Agung Rimba Kurniawan (JRPD (Jurnal Riset Pendidikan Dasar), 2020)
The purpose of this study is to describea how the teacher's perception of the application of Edmodo as a tool for learning activities in Al-Falah Islamic Elementary School Jambi. This research is a study that uses a qualitative approach to the type of phenomenological research. Researchers chose a qualitative approach to the type of phenomenological research because researchers wanted to examine according to phenomena related to teacher perceptions of the application of edmodo as a learning aid in the Al-Falah Islamic Elementary School in Jambi. The informants of this study were nine Al-Falah Jambi Islamic elementary school teachers. Researchers took the "purposive sampling" sampling technique by assigning informants with special characteristics, namely teachers who knew and had used the Edmodo application as a medium or a tool in learning in the network. Data collection techniques used by researchers are questionnaires and interviews. The researcher chose technique triangulation as a test of the validity of the data. By using triangulation techniques, the researchers re-check the data from the same source with different techniques to conduct data analysis. The data obtained were analyzed using the Miles Huberman interactive model which included: data reduction, data presentation, and data verification. The results of this study indicate that the perception of teachers has a percentage of 84.86% and can be categorized as perceptions that strongly agree with the application of Edmodo as a tool for learning activities in primary schools. The teachers felt helped in the learning process using the edmodo application. With the diversity of features found in the Edmodo application, teachers can use it in online learning. The steps of learning to use the edmodo application have not been eliminated or even almost refined so that the teacher feels that the edmodo application is specifically designed for learning in the network. Just as in direct learning there are materials that can be read in the library, assignments, quizzes, correcting students' assignments and even awards given to students. The teacher is also more free because it can be done anytime and anywhere. Teachers' perceptions of the application of Edmodo regarding the constraints are only few namely regarding the programming language. As for the speed of access because online learning all depends on the network, if the network is good the learning will run smoothly. Comfort in learning using the Edmodo application is also felt by the teachers. The teachers have a desire to continue to access Edmodo as a tool for learning activities by adjusting to the needs and learning materials.